Challenges of urban management in a post-conflict situation: the case of Kabul, Afghanistan - Sayed, Sayed Maqbool; Justus Liebig University Giessen (My University, 2017)
The planning system of Kabul City was strongly influenced by the Soviet master planning attempts, which started in the 1960s and continued to prevail until the end of the twentieth century. Despite the Soviet master plans were not fully implemented, their strong impact is still evident in the planning system of Afghanistan.An important event which had an immense negative impact on the development Kabul was the civil war of 1992 -1996, in which, the majority of the city s infrastructure was destroyed and the social fabric of the city was torn apart. This was followed by the five-year rule of the Taliban, which prevented any reconstruction effort.The fall of the Taliban Regime in Afghanistan and establishment of the new government was an important milestone for the development of Kabul City. The relative stability of the post-Taliban Kabul paved the way for vast reconstruction efforts. Meanwhile, the massive return of the refugees and internally displaced people to major cities, especially Kabul, resulted in the emergence of many new challenges. Over seventy percent of the Kabul City area was occupied by informal settlements with no or limited access to basic services and infrastructure. The new situation was involved with conflict of planning ideas for the future of Kabul City. The ideas varied from reviving of the Soviet master plans to new planning solutions for the existing city and as well as the proposal for a new city in the north of the existing Kabul City. The major urban planning and management efforts for post-conflict Kabul includes the preparation of the Development Plan for Kabul in 2008, which was funded by the World Bank and carried out by ICT, an Indian company; revision of ICT plan by JICA team in 2011; and preparation of the Master Plan for Kabul New City in Dehsabz by JICA in 2009. Moreover, several independent construction and reconstruction projects were implemented in Kabul City, which was not part of any of the mentioned large-scale city development plans. The large-scale master plans for Kabul City and Kabul New City were influenced by utopian concepts, which in many cases did not fit to the socio-economic context of Afghanistan. The study and assessment of the various planning and management attempt for post-Taliban Kabul indicate the fact that none of the large-scale master plans did make their way to implementation stages. Therefore, it was concluded that the large-scale top-down city level master plans, despite of consuming large amounts of resources and time, were not able to address the fundamental problems and issues of urban planning and management of post-Taliban Kabul.Nevertheless, feasibility and applicability of smaller scale project have been more than the large-scale utopian concepts. The independent projects have been more efficient and have tangible results. Although, in some cases, the lack of coordination among various city-level projects resulted in the inefficient implementation of some projects and waste of the resources. Therefore, substitution of the prevailing large-scale top-down planning system with a bottom-up system of city planning, based on the coordination of various city-level projects, was suggested and recommended.
Keywords: Kabul; urban planning; urban management; post-conflict; ddc:550